Augmented Reality and Virtual Reality-Based Technology in Cultural Tourism - Daniela Garbin Praničević (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
The paper intends to scrutinize the effects of augmented (AR) reality and virtual reality (VR) technology implementation in cultural tourism. Therefore, the paper explored and presented the following: (i) AR, and VR (AR/VR) based technology concept in general, (ii) AR/VR technologies application in cultural tourism with an emphasis on their potential to protect cultural heritage; (iii) the overview of AR/VR presence in cultural tourism in the 27 European Union countries (EU-27). In the discussion part, besides empirical results based on the EU-27 desk research, AR/VR technologies in cultural tourism are additionally reconsidered from the aspect of climate change. In conclusion, what is encouraged is the application of AR/VR in cultural tourism due to the benefits AR and VR bring in terms of (i) delivering quite substantial content to their visitors any time from any place, (ii) reducing the negative impact of tourism on cultural heritage and (iii) developing related strategies based on more sustainable principles and concepts.
Keywords: O31; O33; Z19; Z32; 330; AR and VR based technology; cultural tourism; sustainable principles; practice issues